Using Regulatory Flexibility to Address Market Informality in Seed Systems: A Global Study - Katrin Kuhlmann; Bhramar Dey (Agronomy, 2021)
Seed rules and regulations determine who can produce and sell seeds, which varieties will be available in the market, the quality of seed for sale, and where seed can be bought and sold. The legal and regulatory environment for seed impacts all stakeholders, including those in the informal sector, through shaping who can participate in the market and the quality and diversity of seed available. This paper addresses a gap in the current literature regarding the role of law and regulation in linking the informal and formal seed sectors and creating more inclusive and better governed seed systems. Drawing upon insights from the literature, global case studies, key expert consultations, and a methodology on the design and implementation of law and regulation, we present a framework that evaluates how regulatory flexibility can be built into seed systems to address farmers’ needs and engage stakeholders of all sizes. Our study focuses on two key dimensions: extending market frontiers and liberalizing seed quality control mechanisms. We find that flexible regulatory approaches and practices play a central role in building bridges between formal and informal seed systems, guaranteeing quality seed in the market, and encouraging market entry for high-quality traditional and farmer-preferred varieties.